SwiftUI tic tac toe online multiplayer game for iOS 15, MVVM (Packt Publishing, 2021)
Learn how to create iOS apps with SwiftUI using MVVM. In this course, we will be building an online multiplayer TicTacToe game with SwiftUI and Firebase. By taking this course, you will learn how to refactor the home view to MVVM. You will explore how to create a game view, building a game grid view and refactoring the game grid view. Furthermore, you will learn how to add the loading indicator and GameView model setup, game logic and model setup. You will understand how to start the game function and firebase service. Learn how to create an alert object and show alerts to the user. The course will cover multiple topics. At the end of this course, you will have an exceptionally good foundation to build on more functions to make this AppStore-ready game.